Why people smoke : an innovative approach to treating tobacco dependence - Leone, Frank T.; Evers-Casey, Sarah (University of Pennsylvania Press, 2023)
"Unique, engaging, and packed with useful clinical vignettes based on twenty-five years of clinical practice. This book will make you a better clinician and will change the way you think about smoking forever. Develop a deeper understanding of our own role in curbing this debilitating public health epidemic"--